The Driver of Whistleblowing Intention and Fraud Prevention: Attitude and The Ethical Culture of The Organization - Lukita Tripermata; Syamsurijal AK Syamsurijal AK; Tertiarto Wahyudi; Luk Luk Fuadah (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
This study aims to examine empirically the phenomenon of direct, indirect, and moderating effects of the relationship between attitude, fraud prevention, whistleblowing intention and organizational ethical culture. The sample of this study consist of 236 Head of the Subdivision of Finance and the Head of the Subdivision of Planning Reporting at the Regional Asset Planning and Finance Agency in five regions throughout Southern Sumatra, namely South Sumatra, Lampung, Bengkulu, Jambi, and Bangka Belitung Islands. This study use Structural Equation Modeling with Amos version 24 to analyze the data. The results of this study show that attitude has a positive effect on fraud prevention, attitude has a positive effect on whistleblowing intention and whistleblowing intention has a positive effect on fraud prevention. The results of this study also show that whistleblowing intention partially mediate the relationship between attitudes and fraud prevention. Besides that, ethical culture of the organization can moderate the positive relationship between whistleblowing intention and fraud prevention